The Role of Pesantren In Countering Radicalism: A Case Study of Indonesia - Nasution, Muhammad Roihan (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The author conducts a metasynthesis and assesses the progress of implementing religious moderation in Indonesia which focuses on the role of pesantren, based on selected research in the 2020-2022 period. In a review of 40 studies related to keywords, it shows the role of pesantren which is quite significant in the fields of education, information and communication media and socio-culture. Pesantren are suggested as centers for dealing with radicalism.